Cholelithiasis in women: particularities of pathogenesis, treatment approaches (literature review and the first experience with own findings) - Yu B Uspenskaya; I V Kuznetsova (IP Berlin A.V., 2013)
The data presented in the article show the relationship between female sex hormones and biliary pathology. The first experience with own findings shows the efficacy of products of ursodeoxycholic acid in combination with cholekinetics or spasmolytics for treatment and prevention of biliary sludge during therapy with female sex hormone products.